2021
DOI: 10.1021/acs.inorgchem.0c03245
|View full text |Cite
|
Sign up to set email alerts
|

Functional Platinum(II) Complexes with Four-Photon Absorption Activity, Lysosome Specificity, and Precise Cancer Therapy

Abstract: Multiphoton materials are in special demand in the field of photodynamic therapy and multiphoton fluorescence imaging. However, rational design methodology for these brands of materials is still nascent. This is despite transition-metal complexes favoring optimized nonlinear-optical (NLO) activity and heavy-atom-effected phosphorescent emission. Here, three four-photon absorption (4PA) platinum­(II) complexes (Pt1–Pt3) are achieved by the incorporation of varied functionalized C^N^C ligands with high yields. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…Nonlinear optical (NLO) phenomena that originated from multiphoton absorption (MPA) are widely applied in tissue imaging and photodynamic therapy, , enabling the use of bio-safe infrared laser light. NLO materials typically undergo processes such as MPA, nonradiative transitions, fluorescence or phosphorescence emission, triplet–triplet annihilation (TTA), and stimulated emission. Organic MPA materials show sizeable MPA properties in a wide range of wavelengths, yet they are usually used in diluted solution, have unstable structures, or experience poor solubility in water. Pure inorganic materials such as quantum dots, nanocrystals, and plasmonic particles present higher stability but perform insufficiently and are usually highly toxic if heavy metal elements are involved. On the other hand, transition-metal complexes offer clear advantages such as plentiful charge transfer, tunable optical properties, and enhanced NLO activities. , Up till now, various kinds of platinum complexes have been designed and synthetized and show excellent performance in experiments and clinical treatments with low toxicity and high selectivity. , As reported by Zhang et al, a series of functional platinum­(II) complexes ( Pt1–Pt3 , as shown in Scheme ) are designed and synthetized, presenting high performance in 4PA activity and precise anti-cancer therapy . In their work, rich experimental results have been presented to show NLO properties and photochemical processes of these complexes through analysis of spectra and assisted by B3LYP/LANL2DZ+6-31G­(d) level calculation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonlinear optical (NLO) phenomena that originated from multiphoton absorption (MPA) are widely applied in tissue imaging and photodynamic therapy, , enabling the use of bio-safe infrared laser light. NLO materials typically undergo processes such as MPA, nonradiative transitions, fluorescence or phosphorescence emission, triplet–triplet annihilation (TTA), and stimulated emission. Organic MPA materials show sizeable MPA properties in a wide range of wavelengths, yet they are usually used in diluted solution, have unstable structures, or experience poor solubility in water. Pure inorganic materials such as quantum dots, nanocrystals, and plasmonic particles present higher stability but perform insufficiently and are usually highly toxic if heavy metal elements are involved. On the other hand, transition-metal complexes offer clear advantages such as plentiful charge transfer, tunable optical properties, and enhanced NLO activities. , Up till now, various kinds of platinum complexes have been designed and synthetized and show excellent performance in experiments and clinical treatments with low toxicity and high selectivity. , As reported by Zhang et al, a series of functional platinum­(II) complexes ( Pt1–Pt3 , as shown in Scheme ) are designed and synthetized, presenting high performance in 4PA activity and precise anti-cancer therapy . In their work, rich experimental results have been presented to show NLO properties and photochemical processes of these complexes through analysis of spectra and assisted by B3LYP/LANL2DZ+6-31G­(d) level calculation.…”
Section: Introductionmentioning
confidence: 99%
“…8,22−24 As reported by Zhang et al, a series of functional platinum(II) complexes (Pt1−Pt3, as shown in Scheme 1) are designed and synthetized, presenting high performance in 4PA activity and precise anti-cancer therapy. 22 In their work, rich experimental results have been presented to show NLO properties and photochemical processes of these complexes through analysis of spectra and assisted by B3LYP/LANL2DZ+6-31G(d) level calculation. In this paper, we present computational results that offer deeper insights into the mechanistic pathways of the photochemical processes and illuminate the geometric and electronic structures that are key to these transitions.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the cases were nonmelanoma skin cancers 1‐3 . Of the chemotherapeutic drugs used in the clinical treatment of cancer, cisplatin (CDDP) was one of the first platinum‐derived drugs discovered and was approved by the U.S. Food and Drug Administration (FDA) in 1979 3‐6 …”
Section: Introductionmentioning
confidence: 99%
“…It is important to note that CDDP nephrotoxicity is dose‐dependent and that trials have shown that low doses of CDDP cause late kidney damage differently than high doses of CDDP 4‐6 . Changes in glomerular filtration were found in 20% to 40% of patients 7 to 10 days after the first dose of CDDP was administered 6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation